Fast Evolving Glioblastoma in a Pregnant Woman: Diagnostic and Therapeutic Challenges - Ivan Bogdanovic; Rosanda Ilic; Aleksandar Kostic; Aleksandar Miljkovic; Filip Milisavljevic; Marija M. Janjic; Ivana M. Bjelobaba; Danijela Savic; Vladimir Bascarevic (Diagnostics)
Background and Clinical Significance: Gliomas diagnosed during pregnancy are rare, and there are no established guidelines for their management. Effective treatment requires a multidisciplinary approach to balance maternal health and pregnancy preservation. Case Presentation: We here present a case of rapidly progressing glioma in a 33-year-old pregnant woman. The patient initially presented with a generalized tonic–clonic seizure at 21 weeks’ gestation. Imaging revealed a tumor in the right cerebral lobe, involving both cortical and subcortical structures, while magnetic resonance spectroscopy suggested a low-grade glioma. The patient remained clinically stable for two months but then developed severe headaches; MRI showed a worsening mass effect. At 34 weeks’ gestation, an emergency and premature caesarean section was performed under general anesthesia. The patient then underwent a craniotomy for maximal tumor resection, which was histologically and molecularly diagnosed as IDH wild-type glioblastoma (GB). Using qPCR, we found that the GB tissue showed upregulated expression of genes involved in cell structure (GFAP, VIM) and immune response (SSP1, TSPO), as well as increased expression of genes related to potential hormone response (AR, CYP19A1, ESR1, GPER1). After surgery, the patient showed resistance to Stupp protocol therapy, which was substituted with lomustine and bevacizumab combination therapy. Conclusions: This case illustrates that glioma may progress rapidly during pregnancy, but a favorable obstetric outcome is achievable. Management of similar cases should respect both the need for timely treatment and the patient’s informed decision.